CAUSES AND CLINICAL-FUNCTIONAL PARAMETERS OF INTRAOCULAR LENS DISLOCATION AFTER CATARACT PHACOEMULSIFICATION. (International journal of medical sciences, 2025)
The causes and clinical and functional parameters of intraocular lens dislocation after cataract phacoemulsification are one of the current problems in ophthalmology. Materials and methods. This study was conducted at the Ophthalmology Department of the Multidisciplinary Clinic of Tashkent State Medical University and “Republican Specialized Scientific-Practical Medical Center of Eye Microsurgery” from September 2024 to September 2025. 21 patients (21 eyes) diagnosed with dislocation of the posterior chamber intraocular lens implanted after cataract phacoemulsification were selected for the study. Patients were divided into two groups. Group 1 (main) - patients with dislocation of the posterior chamber intraocular lens. Group 2 (control) - patients with implantation of the intraocular lens into the posterior chamber. The study included patients (50-80 years old) with posterior chamber intraocular lens dislocation after cataract phacoemulsification. Patients with severe ophthalmological diseases (glaucoma, macular degeneration, diabetic retinopathy) and damage to the organ of vision were excluded. Clinical and instrumental methods were used to comprehensively assess visual functions and the state of eye structures. Results of the study. The study analyzed 21 patients (21 eyes) with posterior chamber intraocular lens dislocation after cataract phacoemulsification. The assessment of clinical and functional indicators made it possible to identify the characteristic features of visual impairment, structural changes in the eyeball, and the frequency of various types of intraocular lens dislocation. Conclusion. The data obtained confirm the leading role of degenerative changes in the bundle of Zinn in the mechanism of intraocular lens dislocation, as well as the importance of early detection and correction of ocular hypertension and macular changes. Optimization of surgical approaches and individual selection of treatment tactics for patients with intraocular lens dislocation are promising areas for further research.